CHARACTER EDUCATION VALUES IN THE NOVEL CHANT ONE MUARA WORKS AHMAD FUADI - Halimah, Siti; Nizan, Muhammad (Jurnal Sabilarrasyad, 2020)
The background of this research is issues in education sector, where values of character education were not poorly highlighted because of tendency toward academic or cognitive concerns. Education currently is more pursuing studentâ€™s graduation target. This research is purposed to develop values of character education that contained in Ahmad Fuadi novel â€œRantau Satu Muaraâ€. This research is qualitative with descriptive analysis method. This research is also using sociology literature approach. Data were collected by researcher where data was recorded and analyzed during periode of research to collect data from novelâ€™s text, then it processed and further analyzed in detailed. Results of this research are values of character education in â€œRantau Satu Muaraâ€ novel by Ahmad Fuadi which are contain values of character education there are religious, hard-driving, nationality, communicative/friendly, reading interest, and responsibility.